14 Interventions to prevent right heart failure in PAH. (9th April 2018) - Tamura, Yuichi
Abstract : Initial treatment strategy for pulmonary arterial hypertension (PAH) has changed from monotherapies to upfront combination therapies. Data from Japan Pulmonary Hypertension Registry (JAPHR), the first organised multi-centre registry for PAH in the country, provide data on real-world treatments and outcomes in Japanese patients. From April 2008 to March 2013, 189 consecutive patients (108 treatment-naïve and 81 background-therapy patients) with PAH were enrolled at 8 centres. We performed retrospective survival analyses and studied the association between upfront combination therapy and haemodynamic improvement, adjusting for baseline NYHA functional class. Among 189 patients, 1-, 2- and 3 year survival rates were 97.0% (95% CI: 92.1 to 98.4), 92.6% (87.0–95.9), and 88.2% (81.3–92.7), respectively. In the treatment-naïve group, 33% of patients received upfront combination therapy. In this cohort, 1-, 2- and 3 year survival rates were 97.6% (90.6–99.4), 97.6% (90.6–99.4) and 95.7% (86.9–98.6), respectively. Patients on upfront combination therapy were 5.27-fold (2.68–10.36) more likely to show haemodynamic improvement at first follow-up compared with monotherapy. According to JAPHR data, initial upfront combination therapy was associated with improvement in haemodynamic status. Also, we performed a prospective study on tolvaptan, a vasopressin receptor antagonist, for right HF associated with PH. Tolvaptan reduced the furosemide dose requirement over a 12 week period in patients with chronic right HF associated with PH in the absence of any serious adverse events. In addition, tolvaptan significantly improved brain natriuretic peptide levels and fluid retention, and was associated with reduced urine osmolality. These findings suggest that tolvaptan can improve right HF.